Filet-o-Fish: Practical and Dependable Domain-Specific Languages for OS Development - Dagand, Pierre-Evariste; Baumann, Andrew; Roscoe, Timothy (Proceedings of the 5th Workshop on Programming Languages and Operating Systems, 2009)
We address a persistent problem with using domain-specific languages to write operating systems: the effort of implementing, checking, and debugging the DSL usually outweighs any of its benefits. Because these DSLs generate C by templated string concatenation, they are tedious to write, fragile, and incompatible with automated verification tools. We present Filet-o-Fish (FoF), a semantic language to ease DSL construction. Building a DSL using FoF consists of safely composing semantically-rich building blocks. This has several advantages: input files for the DSL are formal specifications of the system’s functionality, automated testing of the DSL is possible via existing tools, and we can prove that the C code generated by a given DSL respects the semantics expected by the developer. Early experience has been good: FoF is in daily use as part of the tool chain of the Barrelfish multicore OS, which makes extensive use of domain-specific languages to generate low-level OS code. We have found that the ability to rapidly generate DSLs we can rely on has changed how we have designed the OS.